A Nutrition Education for Productive Aged Women to Improve Knowledge in Preventing Stunting in Indonesia - Meriza Martineta; Nasution, Fitriyani; Lubis, Nenni Dwi Aprianti; Tala, Zaimah Z.; Sari, Dina Keumala (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Background: stunting is one of the double burden health problem in Indonesia and the education during the first 1000 days of life is the most important determining factor. The aim of this study was to improve knowledge in preventing stunting. Methods: 50 women aged 19–59 years were giving a questionnaires before and after nutrition education has been performed. The effect of nutrition education was analyzed using Wilcoxon test. Results: there was a significant change of median score between pretest and posttest (p <0.05). Conclusion: Nutrition education was successful in improving knowledge of productive aged women in reducing stunting.